Roundtable Discussion on COVID-19 Through a Sex and Gender Lens. (1st October 2020) - Legato, Marianne J.; Bennett, Wendy L.; Klein, Sabra; Sheffield, Jeanne S.; Morgan, Rosemary; Decker, Michele R.; Sharps, Phyllis
Although the full and lasting impact of the coronavirus disease 2019 (COVID-19) outbreak is yet to be determined, there is evidence that sex and gender play a significant role in determining patient outcomes across the globe. This roundtable discussion is a transcript of a seminar held by several representatives from Johns Hopkins University on the impact of the global pandemic on women's health and well-being. They reported on the various pathophysiological aspects of the disease, as well as the social and financial consequences of this global pandemic. Looking at COVID-19 through a sex and gender lens highlights the vulnerabilities and inequalities of people of different genders, races, and socioeconomic conditions, and how care providers can better respond to those differences.